Rethinking Nigeria’s soft power capability as a regional leader in Africa - Imo Akanimo Eshiett; Ali Dayıoğlu (Faculty of Social and Political Science, Universitas Airlangga, 2023)
Nigeria has always been seen as a significant regional player in Africa, and the country has not hidden its aspiration to be its leader. However, recent events, particularly in the fourth republic between 1999 and to date, have seen this ambition decline significantly. The study interrogates Nigeria’s soft power leadership capability as contemporary power diffusion theory and its ambition to be a regional leader in Africa. It examines various ways Nigeria can rethink its soft power strategies to achieve its age-long regional aspiration. The qualitative research method was adopted for the study, while primary and secondary sources were used in collecting data for the research. Findings reveal that Nigeria’s neglect and underutilisation of its strategic soft power tools in gaining regional influence continue to inhibit its African leadership ambitions. The study recommends a dynamic policy of developing and deploying significant soft power resources to boost Nigeria’s leadership in Africa.